Značaj i karakteristike istraživanja naziva za boje na primeru japanskog jezika (Philologia, 2021)
This paper aims to illustrate some reasons for investigating color terms in a language. In doing so, we will concentrate on the finding that color terms and colors do not fully correspond, resulting in the fact that color terms can also influence the status of a color in a given society (and not only in the reverse order), which leads us to the intersections of linguistic, cultural and anthropological influences that can be viewed through color.
Keywords: naziv za boju; boja; japanski jezik; univerzalna simbolika; kultura; povezanost faktora